Consumption feedback and water saving: An experiment in the metropolitan area of Milan - Stefano Clò; Tommaso Reggiani; Sabrina Ruberto (Masaryk University, Faculty of Economics and Administration, 2023)
This paper questions whether informative feedback on consumption can nudge water saving behavioral change. For this purpose, we launched a five-month online information campaign which involved equipping around 1,000 households located in the province of Milan (Italy) with a smart meter. Treated households received monthly reports via email on their per capita daily average water consumption, which included a social comparison component (consumption class size). The difference-in-differences analysis showed that, compared to the control group, treated units reduced their daily per capita water consumption by more than 10 % (22 liters or 5.8 gallons). This additional water saving increased with the number of monthly reports, though it did not persist two months after the campaign expired. The impact of the campaign was heterogeneous across consumption classes, while a Regression Discontinuity Design analysis showed that different feedback on consumption class size differentially affected water saving at the margin. Finally, being able to observe the email opening rate, we complemented the ITT analysis by developing a Per Protocol (PP) analysis, where non-adherent units were excluded from the treated group. Both ITT and PP provide consistent conclusions, thus augmenting the level of confidence in the study results.
Keywords: C93; H41; L95; Q25; 330; water saving; nudging; field experiment; online information campaign; information feedback